PENINGKATAN LITERASI KEUANGAN DAN KEWIRAUSAHAAN BAGI NELAYAN DI DESA BENTENG, KECAMATAN LASALIMU, KABUPATEN BUTON - Muhammad Rais; La Ode Muhammad Hasrul Adan (JICS : Journal Of International Community Service, 2025)
The financial literacy and entrepreneurship improvement program for fishermen in Benteng Village, Lasalimu District, Buton Regency aims to enhance fishermen’s household financial managem ent skills and promote economic independence through productive, lo cally based enterprises. The main problems faced by fishermen include a lack of understanding of financial planning and record-kee ping, unstable seasonal income management, and limited entrepreneu rial skills to diversify income sources. The program was implemented through counseling, training, and continuous mentoring that actively involved the fishing community. The training materials covered basic financial management, saving and investment strategies, and access to formal and informal financial institutions. The results indicated a significant increase in participants’ understanding of financial mana gement, along with rising motivation to start small businesses such as seafood processing & local trade. Overall, the program successfully improved financial awareness, strengthened entrepreneurial, & contr ibuted to sustainable economic welfare among coastal communities.